The Presence of an Iron-Sulfur Cluster in Adenosine 5'-Phosphosulfate Reductase Separates Organisms Utilizing Adenosine 5'-Phosphosulfate and Phosphoadenosine 5'-Phosphosulfate for Sulfate Assimilation - Kopriva, Stanislav; Büchert, Thomas; Fritz, Günter; Suter, Marianne; Benda, Rüdiger; Schünemann, Volker; Koprivova, Anna; Schürmann, Peter; Trautwein, Alfred X.; Kroneck, Peter M. H.; Brunold, Christian (My University, 2002)
It was generally accepted that plants, algae, and phototrophic bacteria use adenosine 5'-phosphosulfate (APS) for assimilatory sulfate reduction, whereas bacteria and fungi use phosphoadenosine 5'-phosphosulfate (PAPS). The corresponding enzymes, APS and PAPS reductase, share 25-30% identical amino acids. Phylogenetic analysis of APS and PAPS reductase amino acid sequences from different organisms, which were retrieved from the GenBankTM, revealed two clusters. The first cluster comprised known PAPS reductases from enteric bacteria, cyanobacteria, and yeast. On the other hand, plant APS reductase sequences were clustered together with many bacterial ones, including those from Pseudomonas and Rhizobium. The gene for APS reductase cloned from the APS-reducing cyanobacterium Plectonema also clustered together with the plant sequences, confirming that the two classes of sequences represent PAPS and APS reductases, respectively. Compared with the PAPS reductase, all sequences of the APS reductase cluster contained two additional cysteine pairs homologous to the cysteine residues involved in binding an iron-sulfur cluster in plants. Mössbauer analysis revealed that the recombinant APS reductase from Pseudomonas aeruginosa contains a [4Fe-4S] cluster with the same characteristics as the plant enzyme. We conclude, therefore, that the presence of an iron-sulfur cluster determines the APS specificity of the sulfate-reducing enzymes and thus separates the APS- and PAPS-dependent assimilatory sulfate reduction pathways.